Demographic changes in Portugal at the turn of the 21st century. - Maślanka, Jadwiga (Bulletin of Geography. Socio-economic Series, 2007)
The article discusses demographic changes taking place in Portugal at the turn of the 21st century. Based on statistical data derived from the most recent national censuses of population conducted in years 1991 and 2001, variations in the situation and structure of population were analysed, also by gender and age, while taking into account processes such as feminization or ageing of the society. Portugal is a small country in area terms, but its demographic structure is rather diverse. This diversity stems from different geographical and natural determinants, as well as socio-economic and historio-political factors that operated and are still active in the country.